2020
DOI: 10.1039/d0ra00778a
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemical detection of clozapine by RuO2 nanoparticles-modified screen-printed electrode

Abstract: This study introduces the sensitive electrochemical detection of clozapine with the use of a ruthenium(iv) oxide nanoparticle (RuO2 NP)-modified screen-printed electrode (RuO2 NPs/SPE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Over the last years, the development of electrochemical sensors based on nanomaterial-modied electrodes, has become one of the most active research areas. [49][50][51] A diversity of nanomaterials with wellcontrolled physicochemical features, surface charge, shape and dimension are produced by signicant advances in synthetic methodologies. 52,53 There are many types of nanomaterials employed for the modication of electrodes for electrochemical sensing of HZ including: carbon based nanomaterials carbon nanotubes (CNTs), graphene (GR), metal and metal oxide nanoparticles (NPs) and their composites, and so on.…”
Section: Cme Possessing Nanomaterials For Detection Of Hzmentioning
confidence: 99%
“…Over the last years, the development of electrochemical sensors based on nanomaterial-modied electrodes, has become one of the most active research areas. [49][50][51] A diversity of nanomaterials with wellcontrolled physicochemical features, surface charge, shape and dimension are produced by signicant advances in synthetic methodologies. 52,53 There are many types of nanomaterials employed for the modication of electrodes for electrochemical sensing of HZ including: carbon based nanomaterials carbon nanotubes (CNTs), graphene (GR), metal and metal oxide nanoparticles (NPs) and their composites, and so on.…”
Section: Cme Possessing Nanomaterials For Detection Of Hzmentioning
confidence: 99%
“…The CPs have charge mobility along with their p-electron backbones that handle their uncommon electronic features such as lower energy optical transition, better electrical conductivity, higher surface area, high electron affinity, and mechanical exibility. [22][23][24][25][26][27][28] The most effective parameters constructing the physical properties of CPs are conjugation length, degree of crystallinity, and intra-and interchain interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of water contamination is from drug manufacturers, organic materials, and industry and pharmaceutical residues. Notably, the WHO reported that about 30% of the individuals living need far and wide-ranging clean water sources, and more than 2 000 000 humans die each year by drinking contaminated water. Clioquinol (CQ), associated with the family of hydroxyquinolines, manifests multiple mechanisms of action, stimulating its wide use in medical and pharmaceutical fields. The pharmacological functions of CQ are diversified into topical antiseptics, antiparasitics, and therapeutics for malignancy and intestinal infections. , Because of its ionophore properties and its ability to form lipophilic chelates with divalent metal cations, CQ emerges effectively as a potential therapy for Alzheimer’s, Huntington’s, and Parkinson’s diseases.…”
Section: Introductionmentioning
confidence: 99%